Controle externo dos gastos públicos: uma análise do gasto com pessoal do Distrito Federal após a Lei de Responsabilidade Fiscal - de Souza, Carlos Alexandre (2020)
Among the expenditures of the Federal District, personnel expenses are more representative. In order to control this expense, an LRF arises, imposing limits for a personnel expense. This context is an estimate of the cost of the Federal Federals after the publication of the LRF. The research is descriptive and presents a documentary analysis in the Reports of Fiscal Management and of the Liabilities of the Audit Courts of the Union and the Federal District. The analysis was performed with the purpose of updating and updating its capacity to generate and update the average of the last years of TCU and TCDF. The same occurred in 2011, 2017, the executive power that had the greatest impact on its participation, having reached the ceiling of all the four-month periods of 2011 in 2017. The Legislature adopted different limits of the LRF during a certain period, due to the difficulty interpretation of the nature of the DF, considered hybrid. For example, to study whether external control, through the courts, is fiscally and informative, when the expenditure analysis is done and the issuing of alert limits to the managers of all powers.